Some Properties of Algebraically Paranormal Operator - Rashid, Zaman Adel; Ahmed, Buthainah A.A. (Iraqi Journal of Science, 2022)
Through this study, the following has been proven, if is an algebraically paranormal operator acting on separable Hilbert space, then satisfies the ( ) property and is also satisfies the ( ) property for all . These results are also achieved for ( ) property. In addition, we prove that for a polaroid operator with finite ascent then after the property ( ) holds for for all .